The harder firms practice strategic management, the better they are 1. (10th September 2020) - Elbanna, Said; Al Katheeri, Bakheet; Colak, Mustafa
Abstract: The integrated practice of strategic management, that is the use of the three components of the strategic management process (formulation, implementation, and evaluation) does matter. Firms should plan intensively and pay attention to choosing strategic planning tools that best fit their needs. No matter how sound the formulated plans are, firms will not benefit if these plans are neither implemented nor evaluated correctly. The harder firms practice strategic management, the better their performance and competitiveness will be.